Serum-derived exosomal microRNAs as biomarkers for postoperative delirium - Maokai Xu; Yingjie Chen; Yujun Lin; Danfeng Wang; Xiaochun Zheng (Frontiers in Neuroscience)
IntroductionPostoperative delirium (POD) is a frequent and challenging complication in elderly surgical patients, marked by abrupt cognitive and attentional disturbances. Current POD diagnosis depends on clinical assessments that are time-intensive and lack predictive accuracy before surgery. Although previous research has explored biomarkers such as neuroinflammatory factors and Alzheimer’s-related proteins to enhance POD prediction, single molecular markers have proven insufficient for reliable prognosis.MethodsThis study investigated serum exosomal miRNA expression profiles in postoperative patients to assess their association with POD. We compared miRNA expression between POD and non-POD groups through cognitive assessments and serum analyses. Additionally, enrichment analysis was conducted to determine the biological pathways regulated by differentially expressed miRNAs.ResultsOur analysis identified 57 miRNAs with significantly altered expression between POD and non-POD patients, including 16 upregulated and 41 downregulated miRNAs in the POD group. Enrichment analysis revealed that these miRNAs are involved in genes regulating neurotrophin signaling, neuroactive ligand-receptor interactions, and pathways that influence neuronal plasticity and cell viability.DiscussionThis study highlights specific miRNAs as potential biomarkers for POD and suggests their involvement in the underlying mechanisms of cognitive decline following surgery. By enhancing diagnostic capabilities and identifying potential therapeutic targets, our findings could lead to more effective POD management strategies for elderly patients. Further research is recommended to validate these miRNAs and evaluate their clinical utility for predictive screening and therapeutic interventions.